Mathematical modelling case studies and projects - Caldwell Jim; Ng Douglas K S (Dordrecht Kluwer Academic, 2004)
This book deals completely with Case Studies and Projects. The Case Studies and Projects involve Mathematical and Computational Methods from the three key areas of ODEs, PDEs and Optimization.
Keywords: Mathematical models